2009
DOI: 10.1590/s0102-09352009000300016
|View full text |Cite
|
Sign up to set email alerts
|

Valores hematológicos de bugios pretos (Alouatta caraya) de vida livre da região do Alto Rio Paraná, sul do Brasil

Abstract: Valores hematológicos de bugios pretos (Alouatta caraya) de vida livre da região do AltoRio Paraná, sul do Brasil [Hematologic values of free-ranging black-and-gold 46±3.53 and 36.69±3.54%) and plasma total protein (7.91±0.53 and 7.40±0.63g/dL) were lower in juveniles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
(6 reference statements)
2
6
1
2
Order By: Relevance
“…In general, the parameters evaluated here are comparable to those reported for this species in captivity in Brazil [Santos, ] and when compared to data obtained from free‐ranging specimens by Flaiban et al [], except in leukocyte counts. Both genders exhibited leukocytosis and neutrophilia, with specimens exhibiting higher values at capture in both genders and at captivity in females (see Table .).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In general, the parameters evaluated here are comparable to those reported for this species in captivity in Brazil [Santos, ] and when compared to data obtained from free‐ranging specimens by Flaiban et al [], except in leukocyte counts. Both genders exhibited leukocytosis and neutrophilia, with specimens exhibiting higher values at capture in both genders and at captivity in females (see Table .).…”
Section: Discussionsupporting
confidence: 87%
“…Nonetheless, results presented in those studies should be more specific to the primates they evaluated; it is necessary to consider many other factors, such as nutritional condition, physiological variations, age group, stress, and conditions of captivity [Almosny, ]. The sex variation for several of the parameters, as observed in this study, has previously been reported for other primate species [Flaiban et al, ; Kagira et al, ; Larsson et al, ; Moore, ; Santos, ; Takeshita et al, ; Thrall, ; Wirz et al, ] and is mainly due to hormonal influence because testosterone stimulates erythropoiesis, whereas estrogen inhibits erythropoiesis [Kagira et al, ; Wirz et al, ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The hematological and blood biochemical values of free-ranging animals can help in the diagnosis of some diseases, especially when other factors are taken into account that may infl uence these values like gender, age, stress, or anesthetic agents (FLAIBAN et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The three females of group D were anesthetized with a combination of Tiletamine and Zolazepam (Zoletil® Virbac Brazil) at a dose of 5.5 mg/kg intramuscularly (Flaiban et al 2009). Once tranquilized, all three females received a subcutaneous implant, containing 2.35mg of deslorelin acetate (Suprelorin® Peptech Animal Health, Australia).…”
Section: Implant Application and Removalmentioning
confidence: 99%